Incarceration experiences among a community-recruited sample of injection drug users in Bangkok, Thailand - Lai Calvin; Suwannawong Paisan; Kaplan Karyn; Fairbairn Nadia; Milloy M-J; Hayashi Kanna; Wood Evan; Kerr Thomas (BMC Public Health, 2009)
Abstract Background Since 2003 Thailand has waged an aggressive "war on drugs" campaign focused on arresting and incarcerating suspected drug users and dealers. However, little is known about incarceration experiences among IDU in the wake of the recent war on drugs. Therefore, we sought to examine incarceration experiences among IDU in Bangkok, Thailand. Methods We examined the prevalence of incarceration among community-recruited IDU participating in the Mitsampan Community Research Project. Multivariate logistic regression was used to identify factors associated with a self-reported history of incarceration. We also examined the prevalence of injection drug use and syringe sharing within prisons. Results 252 IDU were recruited in August 2008; 66 (26.2%) were female and the median age was 36.5 years. In total, 197 (78.2%) participants reported a history of incarceration. In multivariate analyses, reporting a history of incarceration was associated with a history of compulsory drug treatment (adjusted odds ratio [AOR] = 4.93; 95% confidence interval [CI]: 1.95 - 12.48), non-fatal overdose (AOR = 3.69; 95%CI: 1.45 - 9.39), syringe sharing (AOR = 2.20; 95%CI: 1.12 - 4.32), and female gender (AOR = 0.41; 95%CI: 0.20 - 0.82). Among those who reported a history of incarceration, 59 (29.9%) reported injection drug use in prison, and 48 (81.4%) of these individuals reported sharing syringes in prison. Incarceration was not associated with the number of injections performed in the previous week (p = 0.202). Conclusion Over three-quarters of the IDU participating in this study reported a history of incarceration, and 30% of these individuals reported injection drug use within prison. Further, an alarmingly high level of syringe sharing within prison was reported, and incarceration was not associated with reductions in drug use. These findings provide further evidence of the need for community diversion strategies, as well as harm reduction programs, in Thai prisons.